Strategi Pengembangan Eduwisata Aloeland di PT Mount Vera Sejati Kabupaten Gunung Kidul - Husyairi, khoirul Aziz; Nurindra, Asrisah; Herlinawati, Agtris; Firmansyah Hs Chandra Praja, Muhammad Rizky (Jurnal Sosial Terapan, 2025)
AloeLand is an agribusiness-based educational tourism initiative developed by PT Mount Vera Sejati, integrating aloe vera cultivation with educational tourism activities. This study aims to analyze the existing business model, examine internal and external factors influencing its development, and formulate appropriate strategic recommendations. The findings indicate that AloeLand possesses strengths in diverse customer segments and multiple revenue streams, yet faces challenges related to market segmentation, human resource management, and the lack of standardized operational procedures. Opportunities are identified in the rising interest in educational tourism and potential collaborations with academic institutions, while threats include increasing competition from similar destinations. Strategic recommendations include enhancing aloe vera–centered educational content, strengthening digital engagement, diversifying tourism programs, and improving internal governance. These strategies are expected to improve AloeLand’s competitiveness and ensure its long-term sustainability.